"GatorSign" for severe lumbar spinal canal stenosis: Magnetic resonance imaging evidence of lumbar perineural edema in the central canal. (4th July 2022) - Persaud-Sharma, Dharam; Mason, Ashlyn; Kumar, Sanjeev
Lumbar spinal stenosis is one of the most commonly diagnosed pathological conditions of the spine. Patients with lumbar spinal stenosis can be symptomatic or asymptomatic. Regardless of the clinical presentation, a combination of radiological imaging modalities including magnetic resonance imaging, CT, and dynamic X-rays can be used to evaluate the severity. An often underrecognized aspect of severe lumbar spinal stenosis is its effect on nerve roots. We propose coining the term "GatorSign" to describe nerve root edema above the area of severe central canal stenosis. This radiological finding can help identify patients with severe central canal stenosis in patients who would likely be neurologically symptomatic, requiring an invasive intervention such as epidural injections or surgical decompression for relief as conservative treatments such as physical therapy and/or medications are less likely to be effective.